Insufficiency of Antenatal Ultrasonographic Examination to Detect Major Congenital Abnormalities in the Presence of Severe Oligohydramnios: A Case Report - Altay, Metin; Karadeniz, Sinan; Erol, Okyar; Karasu, Yetkin; Gelişen, Orhan; Haberal, Ali (Gynecology Obstetrics & Reproductive Medicine, 2008)
Twenty years old patient was referred to our clinic from another state hospital with the diagnosis of oligohydramnios and intrauterin growth restriction (IUGR). After ultrasonographic examination the decision for abdominal delivery was made with the diagnosis of oligohydramnios plus IUGR and abnormal Doppler measurement. The patient was delivered a baby with multiple congenital abnormalities by cesarean section. These abnormalities were not detected by ultrasonography before the decision of delivery. Therefore we decided to present this case in order to emphasize the insufficiency of ultrasonographic examination to detect major congenital abnormalities in the presence of severe oligohydramnios.